Outcome of a dog undergoing definitive‐intent intensity‐modulated radiation therapy for an intranasal ganglioneuroma. Issue 5 (15th June 2020) - Kitagawa, Keita; Reich, Sessaly N.; Desai, Noopur; Policelli, Rachel; Zimmerman, Annie; Sledge, Dodd; Vilar Saavedra, Paulo
Abstract: An 11‐year‐old intact male Shiloh Shepherd was presented for evaluation of epistaxis, decreased nasal airflow, and destructive caudal nasal lesion identified using CT. Histopathologic evaluation of the nasal mass was consistent with a ganglioneuroma. The dog was treated with 10 × 4.2 Gy using IMRT technique. Post radiation therapy (RT), improvement in clinical signs were noted. Tumor progressed in size based on CT evaluation at 49 days, 3, and 6 months post‐treatment. A grade 2 oral mucositis was the only RT side effect noted. Radiation therapy as described above was completed without evidence of high‐grade radiation toxicities and has potential to improve clinical signs but failed to induce tumor response.